Evaluasi Terhadap Asumsi Teoritis Individualisme dan Kolektivisme: Sebuah Studi Meta Analisis - Tjipto Susana (Faculty of Psychology, Universitas Gadjah Mada, 2006)
Since Hofstede (1980) published his research about individualism-collectivism differences among countries, interest in cross-cultural study increased dramatically. However not all studies support each other. So the purpose of this study is to evaluate primary studies that studied individualism-collctivism differences. Articles selected from electronic data¬base (e.g. Proquest, EBSCO, and ERIC) for publication. Forty nine studies were found, but only 15 studies that were relevant. After final evaluation, only 3 studies with 7 data points that actually could be analized. This study found that there are diffe-rences between individualist and collectivist countries in horizontal collectivism. People in collectivist countries are more collectivist than people in individualist countries. In vertical individualism, horizontal indivi¬dualism, and vertical collectivism dimension, homogeneity coefficient (Q) shows that sample drawn from the same source differ systematically. However we can not do moderator analysis because of number of studies are limited. Thus, this study can not explain moderator variables that influence effectc size variation. Keywords: Individualism, Collectivism, meta-analysis.